GERAK DAN KARAKTER TARI PADA TOKOH WIBISANA DALAM LAKON SMARATAPA WAYANG ORANG KAUTAMAN - Dwi Ariyani; Katarina Indah Sulastuti (Greget, 2019)
Motion research and characters dance on the character Wibisana in the Lakon Smaratapa Wayang Orang Kautaman is reviewing the issues of the form of Wibisana character, motion and character dance in the Wibisana figures in the Lakon Smaratapa on October 19, 2018 at the Teater Besar ISI Surakarta. These two problems are examined using several concepts. Analysis tool to examine the form of Wibisana figures, using the verbal and nonverbal concepts by Maryono. Dance and character discussion on Wibisana figures using the concept of motion arrangement by Dorris Humprey, as well as the concept of character in Wayang Kulit, there are three types of characters: typology, temperanment, and character. The research also seeks to examine the sense of taste from the cast of the characters outlined in the concept of sengguh, lungguh, and mungguh. This research is qualitative, data collected through observations, interviews, library studies, and data analysis. The result of the study was first, Wibisana was one of the characters of Wayang Kulit Purwa in Ramayana Epic, the presentation of the form refers to Wayang kulit which is seen from Antawecana, motion, makeup, and fashion. Secondly, it is known that the cultivation of motion and the character of the dance is based on the motion of the alus banyu mili and is given an emphasis on the motion that brings out the character of the dance figure Wibisana that Alus Lanyap Wibisana characters are also supported by vocals in the form of tembang and antawecana. The discussion of Wibisana’s character is seen from the background, known that his character is authority, defending truth, good, and willingly sacrificing. Keywords: forms of servings, motion, dance characters.